2004
DOI: 10.1007/s00421-004-1094-5
|View full text |Cite
|
Sign up to set email alerts
|

Reduced sensations of intensity of breathlessness enhances maintenance of intense intermittent exercise

Abstract: To identify the effect of normal breathlessness sensation elicited during intense intermittent exercise at exhaustion on limitation of exercise maintenance (Ex), the contribution of the flow-resistive unloading effect of normoxic helium-oxygen breathing on the breathlessness sensation to the change in the Ex was examined. Seven men repeatedly performed 12-s exercise at 160% maximal aerobic power output followed by passive recovery for 18-s under normal (CON) and unloaded (UL) breathing conditions until exhaust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 18 publications
2
14
0
Order By: Relevance
“…Such findings implied that the addition of the specific IM warm-up, preferably the one in IMW, to a whole-body warm-up protocol could subsequently improve the tolerance of the intense intermittent run by lessening of the exercise-induced noxious breathlessness sensation. Further, the findings enriched our notion reported in previous studies that the noxious breathlessness sensation elicited during intense intermittent exercise at exhaustion in normal active persons plays a part in limiting the exercise maintenance (Tong et al 2003a(Tong et al , 2004. In the previous studies, the mode of exercise selected was cycling.…”
Section: Breathlessness Sensation and Intense Intermittent Runsupporting
confidence: 86%
See 4 more Smart Citations
“…Such findings implied that the addition of the specific IM warm-up, preferably the one in IMW, to a whole-body warm-up protocol could subsequently improve the tolerance of the intense intermittent run by lessening of the exercise-induced noxious breathlessness sensation. Further, the findings enriched our notion reported in previous studies that the noxious breathlessness sensation elicited during intense intermittent exercise at exhaustion in normal active persons plays a part in limiting the exercise maintenance (Tong et al 2003a(Tong et al , 2004. In the previous studies, the mode of exercise selected was cycling.…”
Section: Breathlessness Sensation and Intense Intermittent Runsupporting
confidence: 86%
“…However, the findings in the present study revealed that such mechanical advantage of the upright bodily position in breathing did not attenuate the limitation of the noxious breathlessness sensation elicited during intense intermittent run in exercise tolerance. In light of the current findings and those in our previous studies (Tong et al 2003a(Tong et al , 2004, it was noted that the noxious breathlessness sensation elicited during intense intermittent exercise at exhaustion in normal active persons may play a role in limiting the exercise tolerance regardless of whether the exercise was cycling or running.…”
Section: Breathlessness Sensation and Intense Intermittent Runmentioning
confidence: 69%
See 3 more Smart Citations